Economic Development Theory of Ibnu Khaldun: Interrelation between Justice and Umran al-Alam - Mafrudlo, Ahmad Mahfudzi; Mansur, Zuhratul Aini; Mustofa, Mustofa; Janwari, Yadi (Share: Jurnal Ekonomi dan Keuangan Islam, 2024)
ABSTRACT – Leading Islamic thinker, Ibn Khaldun, proposed a nuanced theory of economic development that transcends mere material advancement. This theory integrates Islamic principles within a comprehensive framework. This study aims to delve deeper into Ibn Khaldun's economic development theory, focusing on its emphasis on the Islamic way of life and the concept of Umran al-Alam (prospering the earth). A descriptive analysis methodology was employed through a review of existing literature. Ibn Khaldun outlines eight key suggestions and various variables for achieving economic development. Significantly, he underscores the importance of Umran al-Alam, highlighting humanity's responsibility to cultivate the earth. From an Islamic perspective, economic development should prioritize socio-economic justice and maintain a balance between communal well-being and a healthy economy. This study contributes to a more profound understanding of Islamic economic thought and its potential connections to contemporary notions of sustainable development. Further research opportunities lie in exploring the practical applications of Ibn Khaldun's theories within Islamic economic models.==============================================================================================================ABSTRAK – Teori Pembangunan Ekonomi Perspektif Ibnu Khaldun: Interelasi Keadilan dan Umran al-Alam. Pemikir Islam terkemuka, Ibn Khaldun, menawarkan teori pembangunan ekonomi yang lebih bernuansa, tidak sekedar diukur dari sesuatu yang bersifat materi semata-mata. Teori ini mengintegrasikan prinsip-prinsip Islam ke dalam kerangka kerja yang komprehensif. Studi ini bertujuan untuk menggali secara dalam teori pembangunan ekonomi Ibn Khaldun, khususnya pada cara hidup Islami dan konsep "umran al-Alam" (pemakmuran bumi). Kajian ini menggunakan metodologi analisis deskriptif dengan data-data dari sejumlah literatur tersedia. Ibn Khaldun menguraikan delapan komponen inti dan sejumlah variabel untuk mencapai pembangunan ekonomi dimaksud. Ibnu Khaldun menggarisbawahi pentingnya umran al-Alam, yang menyoroti tanggung jawab manusia dalam memakmurkan bumi. Dari perspektif Islam, pembangunan ekonomi harus memprioritaskan keadilan sosial-ekonomi dan menjaga keseimbangan antara kesejahteraan bersama dan sistem ekonomi yang sehat. Studi ini berkontribusi pada pemahaman yang lebih mendalam tentang pemikiran ekonomi Islam dan potensi hubungannya dengan konsep pembangunan berkelanjutan kontemporer. Peluang penelitian lebih lanjut terletak pada eksplorasi aplikasi praktis teori-teori Ibn Khaldun dalam model ekonomi Islam.